European Parliament elections report on media and survey data (BE-DE-EL-IE-PT-SP). Post-election Study - Lobo, Marina Costa (2020)
This report is part of MAPLE Project, ERC – European Research Council Grant, 682125, which aims to study the Politicisation of the EU before and after the Eurozone Crisis in Belgium, Germany, Greece, Ireland, Portugal and Spain. In the preparation of the 2019 EP elections we were able to implement two studies- one that covered one month of online newspaper data during the election campaign, another an online survey that is representative of the population in the six countries covered in MAPLE. In the report on the media, we offer a preliminary analysis of the salience that the EU had during the 2019 EP election in the online news media of Belgium, Germany, Greece, Ireland, Portugal and Spain. In the online survey report, we offer an analysis of attitudes towards national and EU issues of representative samples of the population.